FREQUENCY AND RISK FACTORS FOR OVERUSE INJURIES OF LOWER EXTREMITY IN SLOVENIAN RECREATIVE RUNNERS - Branko Škof; Vedran Hadžić; Edvin Dervišević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Running is probably the most frequent form of regular physical activity in the general population. Unfortunatelly the running related injuries are also quite frequent and different authors are reporting the injury rates between 19,4 % to 79,3 % (Knobloch, Yoon, & Vogt, 2008). The purpose of our cross-sectional study was to evalute the injury rates and anatomical distribution of lower extremity injuries in slovenian runners of different gender, age and training level. Unique injury report form was used to evaluate data of 1.323 recreative runners (50.3 % females and 49.7 % males, average age 37.8 ± 10.9 let). The results have shown that: - During the previous year 53.5 % of runners had experienced at least one running related injury that caused them to miss from regular running for at least one week. - The proportion of uninjured female runners during the previous year was significantly lower when compared to male runners (59.1 % females vs. 40.9 % males, Chi square = 0.000) - The age and the running training volume were not related with injury rates. - The injury rates were related with the training level (Chi square = 0.024), which means that well trained runners had less injuries compared with less trained counterparts. Same was surprisingly true for young still unexperienced runners. - The injuries were of acute nature in 59.3 % cases while 28.9 % runners reported overuse injuries - The rate of overuse injuries is increasing with age of the runner as with the over 50y old runners the prevalence of overuse injuries was 40.9 %, while in the below 35y runners the prevalence was only 26.4 % (Chi square = 0.014). The running related overuse injuries of lower extremity are in many cases related to inappropriate training approach (too qucikly, too much; too quickly, too fast).